Faktor-faktor kecenderungan belia Muslim menyertai program pembangunan kerohanian di Universiti Awam Malaysia - Nik Safiah, Nik Abdullah (2019)
Youth should participate in spirituality development programme to build a strong identity. Although many programmes have been organized by various parties, but the tendency of youth to participate is less satisfactory. Hence, this study is conducted to measure the level of tendency of Muslim youth to participate in spirituality development programme and to identify the differences based on demographic characteristics. In addition, this study aims to determine significant factors (attitudes, environmental influences, perceived behavioral control, religous appreciation, spirituality practices, age, rural residence locations and on campus) in influencing level of tendency of Muslim youth to participate in this programme. Furthermore, this study evaluates the effect of moderating factor (religious schools) towards the relationship between the determinants and the tendency to participate. Theory of Planned Behavior and Behavioral Theory from Islamic perspective were applied in this study by using quantitative method through distribution of questionnaires to 623 Muslim youths in public universities. The data was analyzed using independent sample t-test, ANOVA, Pearson correlation, multiple and hierarchical regression. The findings revealed that the level of tendency of Muslim youth to participate in spirituality development programme is moderately high. The level is also significantly different based on age, residence location, type and field in secondary school, academic qualification to enroll, academic program enrolled and on campus factor. Furthermore, attitudes, environmental influences, perceived behavioral control, religious appreciation and demographic characteristics have positive effect to tendency to participate. Interestingly, the religious schools was found to have significant and positive moderating effect on the relationship between the spirituality practices and participation tendency. Thus, educational institutions, families and communities need to encourage and support the youth to participate in the spirituality development programme and give more emphasis to religious education at early stages to ensure a holistic youth development towards nation building of the country.